Exploring landscape ecological risk with human activity intensity and correlation in the Kuye River Basin - Wu, Yihan; Qin, Fucang; Li, Long; Dong, Xiaoyu (Frontiers in Ecology and Evolution, 2024)
IntroductionThe Kuye River Basin, a typical erosion area of the Loess Plateau region with the second largest tributary of the Yellow River Basin, faces significant environmental challenges and intense human activities. Balancing environmental sustainability and economic development in this region is urgent.MethodsTherefore, this study takes this basin as the object and evaluates the landscape ecological risk and human activity intensity from 2000 to 2022 based on land use/land cover, population distribution and nighttime lighting data. And a geographically weighted regression model was used to reveal the correlation between the two.Results and discussionResults showed that the average landscape ecological risk index in 2000, 2015, and 2022 were 9.01×10-4, 5.61×10-4, and 7.40×10-4, respectively. This shows that the overall landscape ecological risk index is low in the first 15 years and then gradually increases over time. Cultivated land, grassland and construction land are the main landscapes, the expansion of 7.95 times construction land is a key factor in the intensification of human activities, mainly concentrated in the northwest, followed by a gradual expansion towards the south-east, and likewise the landscape ecological risks follow the same trend. Medium to high intensity human activities exacerbate landscape ecological risks, with a significant positive correlation, while low intensity human activities cause little damage to landscape ecology. To achieve sustainability, it is necessary to effectively control construction land and improve land use structure. Then, in the planning work, priority will be given to the northwest region with high human activity intensity and high landscape ecological risks, and the governance direction will gradually shift to the southeast region. These findings provide empirical evidence to support decision-making and underscore the need for comprehensive strategies to mitigate landscape ecological risks and promote sustainable development in the Kuye River Basin.